Characteristics of human arm impedances: a study on daily movement - Choudhury, Tasnuva Tabashhum; Rahman, Md. Mozasser; Khan, Md. Raisuddin (2014)
This paper presents the impedance characteristics of human arm in daily spatial activity. Human arm is considered as a mass-spring-damper system. The input data in the form of Cartesian position is measured to get dynamic impedance relationship by the motion equation for the mass-spring- damper system. Mappings are done by various combinations to observe the nature of the different impedance components during dynamic movement. The significant amount of variation in damping and inertia components are observed in every turning of the arm movement while the stiffness shows the changing behavior throughout the movement. From this study it is known that for this particular movement the arm follows a pattern and same behavior is followed for the repetitions of the movement. The obtained result could be beneficial for the study of upper extremity exoskeleton for human rehabilitation.